Fermentation Characterization of Chinese Yam Polysaccharide and Its Effects on the Gut Microbiota of Rats - X. F. Kong; Y. Z. Zhang; X. Wu; Y. L. Yin; Z. L. Tan; Y. Feng; F. Y. Yan; M. J. Bo; R. L. Huang; T. J. Li (International Journal of Microbiology)
Rat was used to characterize Chinese Yam polysaccharides (CYPs). In Exp. 1, maximum volume and rate of gas production in CYP 3-supplemented group were higher than other CYP-supplemented groups and control group, while pH values and NH3 contents in CYP 2-, CYP 3-, and CYP 4-supplemented groups were lower than control group. Contents of acetate, propionate and butyrate increased by supplementing CYP 3 or CYP 4 compared to other groups, except for glucose-supplemented group. Contents of isobutyrate for CYPs groups decreased compared to control group. CYP 3 enhanced beneficial gut microbiota, but suppressed bacterial pathogens. In Exp. 2, contents of acetate and butyrate in cecal digesta of rats fed 0.25 or 0.5 g/kg CYP 3 were higher than other groups on day 7. pH values in 0.25 and 0.5 g/kg groups were lower than 1.0 g/kg group. Contents of acetate in 0.25 and 0.5 g/kg groups were greater than other 2 groups on day 21. Gut microflora in CYP 3-supplemented rats had greater diversity than non-supplemented rats. CYP 3 enriched beneficial gut microbiota, but suppressed bacterial pathogens in rat cecum. These findings suggested that CYP 3 is a good source of carbon and energy, and may improve bacterial community diversity and modulate short-chain fatty acid production in hindgut of rats.